Batman/Superman, world's finest. Vol. 4, Return to kingdom come - Waid, Mark, 1962- (DC Comics, 2024)
"Acclaimed writer Mark Waid returns to the world of Kingdom Come alongside artist Dan Mora in an epic adventure uniting two DC universes! Superman's former protégé, Boy Thunder, is in danger and the only way to rescue him is to bridge the World's Finest universe with one that includes a jaded Superman, a broken Batman, and a war-hungry Wonder Woman....this is the world of Kingdom Come. Up against the villainous Magog, the World's Finest team find themselves trapped in a world on it's way to an apocalyptic future. Will those who once were friends become foes and what will it take to save both universes?"--